Contraceptive Knowledge among Adolescents of a public educational institution in Lima: Conocimiento sobre contraceptivos en adolescentes de una institución educativa pública de Lima - Andrade Tenorio, Edith (2017)
OBJECTIVES: To evaluate the knowledge about contraceptives, its uses, efficacy, and adverse effects in an adolescent’s population of a public high school. MATERIALS AND METHODS: This study is descriptive and cross-sectional. A 13-question test was used, in which was evaluated knowledge about contraceptives and additional demographic information. In the data analysis, descriptive and exploratory techniques were applied with factorial analysis. 333 adolescents participated. The sample was non-probabilistic. RESULTS: The percentage of correct answers in adolescents was 60% with a standard deviation of 13.6%. Women had a higher percentage score than their male counterparts. (63% and 56.7%, p value <0.001, T de Student). There was no correlation between the scores obtained and the age. The level of knowledge was rated as medium with 73.6% and low with 21.6%. Condom was the contraceptive method of which they had better knowledge (88.6%). CONCLUSIONS: The results show that it is necessary to improve the quality of information and knowledge about the proper use of contraceptive methods, which will have an effect positive on the sexual and reproductive health of adolescents.